2018
DOI: 10.3390/molecules23020490
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics of DPP-4 and Its Influence on the Projection of Bioactive Ligands

Abstract: Dipeptidyl peptidase-4 (DPP-4) is a target to treat type II diabetes mellitus. Therefore, it is important to understand the structural aspects of this enzyme and its interaction with drug candidates. This study involved molecular dynamics simulations, normal mode analysis, binding site detection and analysis of molecular interactions to understand the protein dynamics. We identified some DPP-4 functional motions contributing to the exposure of the binding sites and twist movements revealing how the two enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
(87 reference statements)
1
23
0
Order By: Relevance
“…Molecular dynamics (MD) simulations 29 and more recent Normal Mode Analysis approaches 30 , 31 have become major techniques in the arsenal of tools developed to investigate the mode of action of bioactive molecules. A recent approach called MDeNM (molecular dynamics with excited normal modes) has recently been developed using low-frequency normal mode directions in MD simulations 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations 29 and more recent Normal Mode Analysis approaches 30 , 31 have become major techniques in the arsenal of tools developed to investigate the mode of action of bioactive molecules. A recent approach called MDeNM (molecular dynamics with excited normal modes) has recently been developed using low-frequency normal mode directions in MD simulations 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In chain B, it is evident that the substrate binding region and the catalytic dyad of the mutants presented, on average, a higher flexibility in comparison to the wild-type molecule. This asymmetric/distinct behavior between the chains in homodimeric enzymes were also identified by molecular dynamics simulations involving the SARS-CoV-2 M pro [17] and SARS-CoVM pro [41] as well as NMA calculation for HIV-1 protease [42] and DPP-IV diabetes related protein [43]. Thus, this analysis indicated that some mutants may present characteristics that can influence their catalytic activity, substrate binding affinity and/or dimer stability, as also shown previously by Amamuddy et al (2020) [17].…”
Section: Resultsmentioning
confidence: 61%
“…Moreover, K. M. Honorio et al utilized dynamic protein methods to design human DPP4 inhibitors that might fit into the catalytic region. The study shows that human DPP4 functional motion significantly affects the design of such inhibitors (Pantaleão, 2018;Ribeiro & Filizola, 2019). Further, structural and modeling studies of human ACE2 suggest spatial interactions with SARS-CoV-2 might be varied among COVID-19 patients due to genetic variants in ACE2, which leads to susceptibility variations against the virus (Hussain, 2020).…”
Section: Introductionmentioning
confidence: 90%